2003
DOI: 10.1097/00005537-200310000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Bowman‐Birk inhibitor for oral cancer chemoprevention and analysis of neu immunohistochemical staining intensity with Bowman‐Birk inhibitor concentrate treatment

Abstract: ObjectiveslHypothesis: Cancer chemoprevention is a rapidly evolving approach to reverse or inhibit carcinogenesis, and there is active interest in development of effective chemopreventive agents against head and neck cancers. The retinoids are archetypal chemopreventive agents for oral premalignant lesions. They have significant clinical effect, but widespread use is limited by significant clinical toxicity. The Bowman-Birk Inhibitor is one of several nontoxic compounds exhibiting both potent anticarcinogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…BBIC shows promise to become an effective nontoxic chemopreventive agent based on results of extensive preclinical studies, and Phase I and Phase IIa clinical trials. BBIC has dose-related clinical activity against oral leukoplakia and modulates levels of Neu (Neu immune histochemical staining intensity for lesions) and protease activity (Armstrong et al, 2003). Wan et al (1999a) have reported a specific substrate hydrolysis methodology to measure the protease activity of human oral mucosal cells.…”
Section: Naturally-occurring Plant Protease Inhibitors In Clinical Trmentioning
confidence: 99%
“…BBIC shows promise to become an effective nontoxic chemopreventive agent based on results of extensive preclinical studies, and Phase I and Phase IIa clinical trials. BBIC has dose-related clinical activity against oral leukoplakia and modulates levels of Neu (Neu immune histochemical staining intensity for lesions) and protease activity (Armstrong et al, 2003). Wan et al (1999a) have reported a specific substrate hydrolysis methodology to measure the protease activity of human oral mucosal cells.…”
Section: Naturally-occurring Plant Protease Inhibitors In Clinical Trmentioning
confidence: 99%
“…Other proteins or peptides present in lower amounts include enzymes such as lipoxygenase, chalcone synthase and catalase. Peptides such as lunasin (a 43 amino acid protease inhibitor) and the Bowman-Birk inhibitor (a 71 amino acid protease inhibitor) have been reported to have an anticancer capacity or an in vitro chemopreventative effect (Armstrong et al, 2003;Galvez et al, 2001;Lam et al, 2003). Some of the health benefits attributed to soy may result from the release of biologically active peptides by enzymatic proteolysis during gastrointestinal digestion or during the fermentation of soy proteins.…”
Section: Soybean Composition and Isoflavone Biosynthesismentioning
confidence: 99%
“…The same study demonstrated the noncytotoxic effect of BBI when its protease inhibitor activity was removed. This protease inhibitor also demonstrated its in vitro chemopreventive effect on other types of cancer such as oral cavity [36,37] and lung cancer [38,39]. In contrast to previous studies, a [24,25] Suppressed proliferation of breast cancer cells through accumulation of MAPK phosphatase-1 and induction of apoptosis and lysosome membrane permeabilization (20 and 200 μM, in vitro) [26,29] Induced apoptosis in prostate cancer cells through upregulation of Cx43 (500 μg/ml and 2000 mg/kg/day, in vitro and in vivo) [31] Antiproliferative effects on human colon cancer cells μM, in vitro) [33][34][35] Kunitz trypsin inhibitor Suppressed cancer invasion and metastasis through inhibition of uPA expression (10 μM and 50 g/kg diet, in vitro and in vivo) [40,42] Suppressed LPS-induced and UV-induced cytokine production (5 μM, in vitro) [ 163,164] Inducted apoptosis in rat lymphoma cells (5 μg/ml, in vitro) [ Cx43 connexin 43, LPS lipopolysaccharide, UV ultraviolet, uPA urokinase plasminogen activator, MAPK mitogen-activated protein kinase recent study in MDA-MB-231 breast cancer xenograft mouse model showed that BBI given at 20 mg/kg body weight for 2 months at a frequency of three times per week was not able to reduce tumor incidence in mouse [155].…”
Section: Plant Protease Inhibitorsmentioning
confidence: 92%